Does a board characteristic moderate the relationship between CSR practices and financial performance? Evidence from European ESG firms - Matteo Rossi; Jamel Chouaibi; Salim Chouaibi; Wafa Jilani; Yamina Chouaibi (Journal of Risk and Financial Management, 2021)
This study aims to examine the potential effect that corporate social responsibility practices (CSR) have on financial performance in ESG firms, using the moderating role of board characteristics. To test the moderating effect of the board characteristics in the relationship between CSR practices and financial performance, we applied linear regressions with panel data using the Thomson Reuters ASSET4 database from European countries in analyzing data of 225 listed companies between 2015 and 2019. The results show that board characteristics partially moderate the relationship between CSR practices and financial performance in European ESG firms. In addition, this study indicates that CSR practices affect the firm's financial performance positively. The study findings appended a new dimension to governance research that could provide policymakers and regulators with a valuable source of information to strengthen governance mechanisms for better financial performance. Previous studies mostly investigate the direct effect of corporate governance on financial performance. A few studies examine the moderating effect of CSR practice. This paper contributes by investigating the moderating effect of governance mechanisms in the ESG context.
Keywords: 330; corporate governance; financial performance; CSR practice; environmental social and governance (ESG)